Oxidation reaction mechanism of hydrothermal carbon microspheres with applications to transesterification after sulfonation. Issue 1 (23rd September 2022) - Xue, Yuan; Zhao, Xueling; Yuan, Hong; Li, Hui
Abstract: Background: An efficient sulfonic acid‐type acid catalyst with high acid site density based on hydrothermal carbon microspheres (HCMs) has been developed. The reaction by which double bonds in the HCMs were oxidized to generate carboxyl groups was evaluated based on density functional theory calculations. Results: Sulfonic acid‐type HCMs (SHCMs) were prepared from HCMs through a three‐step process comprising oxidation, amidation and sulfonation. An analysis of the oxidation process indicated that the formation of carboxyl groups involved the activation of O2 molecules and CH bonds, the cleavage of CC bonds, the homolytic fission of peroxy acids and the coupling reactions of H radicals. The formation of numerous carboxyl groups on the HCM surfaces was the key to obtaining SHCMs with a high acid density of 14.5 mmol g −1 . Conclusions: The SHCMs obtained exhibited good catalytic performance during the transesterification of waste frying oil with methanol. Reactions performed using a methanol/oil molar ratio of 9:1 at 90 °C for 5 h gave a fatty acid methyl ester yield of 85.56%. © 2022 Society of Chemical Industry (SCI). Abstract :